Biohythane production and microbial characteristics of two alternating mesophilic and thermophilic two-stage anaerobic co-digesters fed with rice straw and pig manure. Issue 6 (January 2021) - Chen, Hong; Huang, Rong; Wu, Jun; Zhang, Wenzhe; Han, Yunping; Xiao, Benyi; Wang, Dongbo; Zhou, Yaoyu; Liu, Bing; Yu, Guanlong
Graphical abstract: Highlights: Biohythane can be produced by anaerobic co-digestion of rice straw and pig manure. The thermophilic-mesophilic systems possessed had high hydrogen and methane yields. Hydrolysis was the rate-limiting step of the thermophilic acid-producing phase. Methanobrevibacter dominated in mesophilic acid-producing phase with a low H2 yield. The thermophilic acid-producing phase provided selective pressure for methanogens. Abstract: To investigate biohythane production and microbial behavior during temperature-phased (TP) anaerobic co-digestion (AcD) of rice straw (RS) and pig manure (PM), a mesophilic-thermophilic (M1-T1) AcD system and a thermophilic-mesophilic (T2-M2) AcD system were continuously operated for 95 days in parallel. The maximal ratio (8.44%v/v) of produced hydrogen to methane demonstrated the feasibility of biohythane production by co-digestion of RS and PM. T2-M2 exhibited higher hydrogen (16.68 ± 1.88 mL/gVS) and methane (197.73 ± 11.77 mL/gVS) yields than M1-T1 (3.08 ± 0.39 and 109.03 ± 4.97 mL/gVS, respectively). Methanobrevibacter (75.62%, a hydrogenotrophic methanogen) dominated in the M1 reactor, resulting in low hydrogen production. Hydrogen-producing bacteria ( Thermoanaerobacterium 32.06% and Clostridium_sensu_stricto_1 27.33%) dominated in T2, but the abundance of hydrolytic bacteria was low, indicating that hydrolysis could be a rate-limiting step. The thermophilic acid-producing phase provided effective selective pressure for hydrogen-consuming microbes, and the high diversity of microbes in M2 implied a more efficient pathway of methane production.